2015
DOI: 10.1021/acs.jpcc.5b04403
|View full text |Cite
|
Sign up to set email alerts
|

Exciton and Free Charge Dynamics of Methylammonium Lead Iodide Perovskites Are Different in the Tetragonal and Orthorhombic Phases

Abstract: The small exciton binding energy of perovskite suggests that the long lived photoluminescence and slow recovery of the ground state bleaching of the tetragonal phase at room temperature results primarily from the decay of free charges rather than the decay of the initially created excitons. Here we demonstrate the ground state bleaching recovery of the orthorhombic phase of methylammonium lead iodide (CH 3 NH 3 PbI 3 ) is much faster than that of the tetragonal phase using temperature dependent transient absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 33 publications
5
78
0
Order By: Relevance
“…[34,35] Within the vicinity of the transition temperature, spatially-resolved PL studies, as well as temperature-dependent XRD measurements, showed that both phases coexist [35,36] and that an energy transfer from the orthorhombic phase to tetragonal inclusions takes place on the picosecond time scale (70 ps). [37] The temperature-dependent changes in the photoluminescence spectra of MAPbI 3 were reported by numerous groups, for both thin films as well as their single crystal counterparts. [16,17,24,[33][34][35][38][39][40] The unusual blue shift in the transition region of the phase transition is, at present, not well understood.…”
Section: Photoluminescencementioning
confidence: 81%
“…[34,35] Within the vicinity of the transition temperature, spatially-resolved PL studies, as well as temperature-dependent XRD measurements, showed that both phases coexist [35,36] and that an energy transfer from the orthorhombic phase to tetragonal inclusions takes place on the picosecond time scale (70 ps). [37] The temperature-dependent changes in the photoluminescence spectra of MAPbI 3 were reported by numerous groups, for both thin films as well as their single crystal counterparts. [16,17,24,[33][34][35][38][39][40] The unusual blue shift in the transition region of the phase transition is, at present, not well understood.…”
Section: Photoluminescencementioning
confidence: 81%
“…28 Since the efficiency of the process decreases at lower temperatures (the transfer rate and the strength of the transfer component decrease with lowering of the temperature, compare Fig. 28 Since the efficiency of the process decreases at lower temperatures (the transfer rate and the strength of the transfer component decrease with lowering of the temperature, compare Fig.…”
Section: Resultsmentioning
confidence: 99%
“…explained in terms of the more efficient higher-order processes of recombination at larger charge carriers densities.16 Figures S7-S10show that the TA and THz decays at the fluence of the absorbed photons of 0.72×10 13 ph/cm 2 are the same, which demonstrates that the observed mobility is due to a drop in the excited charge carriers concentration.16,44 In contrast to the TA decays upon excitation with the fluence of 9.4×10 13 ph/cm 2 , the THz ones do not show the presence of the 6 ps component attributed previously to the decay of excitons population. 16Page 15 of 39 Physical Chemistry Chemical PhysicsPhysical Chemistry Chemical Physics Accepted ManuscriptThus the time-resolved TA data along with the previous reports on the MAPbI 3 , present an evidence for exciton population at high fluences of the absorbed photons 36,45,52. 16Page 15 of 39 Physical Chemistry Chemical PhysicsPhysical Chemistry Chemical Physics Accepted ManuscriptThus the time-resolved TA data along with the previous reports on the MAPbI 3 , present an evidence for exciton population at high fluences of the absorbed photons 36,45,52.…”
mentioning
confidence: 87%
“…The increase in the fluence clearly affects the TA kinetic traces resulting in the appearance of new decaying components and in shortening of the existing ones. 21,31,45 It was reported that the change of methylammonium to formamidinium results in a change in the perovskite band structure giving rise to unbalanced electron and hole mobilities. For all the excitation wavelengths, we can distinguish three processes Figure S5 shows that the ∆OD -2 upon excitation at 400 nm using absorbed pump fluence of 6.9×10 13 ph/cm 2 is linear between 40 -900 ps.…”
Section: Femtosecond Dynamics At 775 Nm Observation Wavelengthmentioning
confidence: 99%